Rebuttal to "density functional theory investigation of site prediction of Fe substitution in barium titanate" - Nimmanpipug P. (2014)
Through this letter to the editor (Rebuttal), we had given our explanation for the queries raised by Professor Juan J. Meléndez commenting on the high substitution energies, the small simulation supercells, and the inconsistence of experimental data and simulation results. We agree with the comment that applying a "chemical potential diagram" is a general way to study defect system. However, there are some experimental concerns on "what the initial materials should be used", whereas many degrees of freedom become feasible. Therefore, the formation energy equation (with foreign atoms substitution) cannot be trivially answered by the formation energy within a chemical potential diagram framework, unlike substitution energy calculated directly from our suggested chemical equation. We explain in the details on our approach and confirm the validity of our main equation; FeO+Ba8Ti8O23→Ba8Ti7FeO23+TiO2 for the substitution energy with 2×2×2 supercell size which the results still show some suggestive trends. © 2014 Elsevier Ltd and Techna Group S.r.l.